2023
DOI: 10.1128/aac.01563-22
|View full text |Cite
|
Sign up to set email alerts
|

The Novel DNA Binding Mechanism of Ridinilazole, a Precision Clostridiodes difficile Antibiotic

Abstract: Clostridioides difficile infection (CDI) causes substantial morbidity and mortality worldwide with limited antibiotic treatment options. Ridinilazole is a precision bisbenzimidazole antibiotic being developed to treat CDI and reduce unacceptably high rates of infection recurrence in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…It was also reported in a preprint that 60 bound to and inhibited several essential promoters on the S. aureus chromosome, potentially indicating multiple MoAs . Another minor groove binder is ridinilazole ( 61 ), a symmetrical head-to-head bis-benzimidazole, which was also previously in development for CDI. , Again, multiple MoAs might be in effect, as RNA-seq data indicated that 61 also had broad effects on multiple C. difficile compartments, particularly pathways involved in energy generation . Ridinilazole ( 61 ) completed two phase 3 trials (NCT03595553, NCT03595566) in 2021, but a prespecified superiority threshold was not met, and Summit has halted further development…”
Section: Compounds With New Antibacterial Modes Of Actionmentioning
confidence: 88%
“…It was also reported in a preprint that 60 bound to and inhibited several essential promoters on the S. aureus chromosome, potentially indicating multiple MoAs . Another minor groove binder is ridinilazole ( 61 ), a symmetrical head-to-head bis-benzimidazole, which was also previously in development for CDI. , Again, multiple MoAs might be in effect, as RNA-seq data indicated that 61 also had broad effects on multiple C. difficile compartments, particularly pathways involved in energy generation . Ridinilazole ( 61 ) completed two phase 3 trials (NCT03595553, NCT03595566) in 2021, but a prespecified superiority threshold was not met, and Summit has halted further development…”
Section: Compounds With New Antibacterial Modes Of Actionmentioning
confidence: 88%